Identifying barriers to care and support: Aging in Central Kentucky. Issue 2 (3rd July 2022) - Guest, M. Aaron; Hunter, Elizabeth G.
ABSTRACT: Gay and lesbian individuals, as they age, may experience trouble navigating the variety of community and social systems that have been put in place to assist older adults. In this study, we worked with the local gay and lesbian communities to identify the most significant challenges facing aging lesbian and gay individuals in Central Kentucky. Data were collected through key informant one-on-one interviews and focus groups. We relied on a community-based snowball approach for participant recruitment. The research team conducted three focus groups (one gay-male focused (n = 3) and two lesbians focused (n = 7)) and eight (n = 8) key informant interviews. Three key themes were found in these interviews, broadly categorized into long-term care, social support, and health care. Initial findings support the further development and expansion of a community-generated needs assessment to understand better the challenges facing aging sexual minority Kentuckians.